TINGKAT PENGETAHUAN PENGGUNA KONTRASEPSI KB HORMONAL TERHADAP EFEK SAMPING PENINGKATAN TEKANAN DARAH DI APOTEK PERINTIS BANJARMASIN - Mochammad Maulidie Alfiannor Saputera; Devia Pratiwi; Anna Khumaira Sari; Noverda Ayuchecaria; Nazhipah Isnani (Jurnal Insan Farmasi Indonesia, 2020)
The level of knowledge of hormonal family planning contraception users is still very low on the side effects that occur in many low-income countries, especially in Indonesia. Most do not know the side effects that often arise in the use of hormonal contraception, one of which is increased blood pressure. The purpose of this study was to determine the level of knowledge of Hormonal contraceptive contraceptive users on the side effects of increasing blood pressure at Banjarmasin Pioneer Pharmacy. This type of research is a prospective descriptive method. The study was conducted in March to April 2019 in three Banjarmasin Pioneer Pharmacy, namely in Kuripan Pioneer Pharmacy, Kayutangi Pioneer Pharmacy and S.Parman Pioneer Pharmacy. The population in this study were patients who bought hormonal birth control contraception and patients who bought antihypertensive drugs taking hormonal contraception. The measuring instrument used in the form of a questionnaire consisted of 10 statements. The sampling technique uses accidental sampling. The results of 132 respondents showed that the level of patient knowledge as many as 46 patients (34.8%) had good knowledge, 66 patients (50.0%) had sufficient knowledge, and 20 patients (15.2%) had less knowledge.